Pengaruh Koneksi Politik & Leverage Terhadap Manajemen laba Pada Perusahaan KOMPAS100: Peran Jumlah Direksi Dan Komisaris Sebagai Variabel Kontrol - Raisha Putri; Ali Riza Fahlevi (Politeknik Ganesha Medan, 2026)
This research investigates the influence of political connections and leverage on earnings management, with the number of directors and commissioners included as control variables in firms listed on the KOMPAS100 index of the Indonesia Stock Exchange over the 2021–2024 period. A quantitative approach with a causal associative design is applied to examine the causal relationships among variables using panel data regression analysis with a Fixed Effect Model (FEM) processed using EViews 14 software. The sample comprises 47 firms with a total of 188 firm-year observations after excluding outliers. Earnings management is proxied by discretionary accruals estimated using the Modified Jones Model, derived from the difference between total accruals and non-discretionary accruals based on adjusted changes in revenue, receivables, and property, plant, and equipment. Political connections are measured through a dummy variable indicating politically connected individuals within the corporate structure, while leverage is proxied by the Debt to Equity Ratio (DER). The findings reveal that political connections do not significantly affect earnings management, whereas leverage has a significant impact. The number of directors and commissioners as control variables is also statistically significant. These results suggest that corporate governance mechanisms play a more dominant role in explaining earnings management in KOMPAS100 firms than political connections and capital structure.